CORRECTION OF THE LIVER MORPHO-FUNCTIONAL STATE IN EXPERIMENTAL NON-ALCOHOLIC STEATHEPATITIS AND HYPERCHOLESTERINEMIA - Yakimenko, O.O.; Appelhans, O.L.; Maznichenko, Ye.O. (World of Medicine and Biology, 2019)
The purpose of the work was to study the dynamics of morphological and functional changes in the liver during complex lipid-lowering therapy in NASH with hypertension in rats. The study was carried out on the Wistar line rats. The animals were divided into groups: intact; control for NASH and HCh; I - rats with NASH and HCh treated with rosuvastatin "Rosuvastatin IS" 0.3 mg / kg per day, 45 days; II - rats with NASH and GB treated with rosuvastatin 0.3 mg / kg per day and omega-3 PUFAs (Epadol Neo), 45 days; III - rats with NASH and HCh receiving rosuvastatin 0.3 mg / kg per day and hepatoprotector "Gepadif", 45 days. Modeling of the pathology occurred 90 days through the use of an atherogenic diet. Animals were removed from the experiment on the forty-fifth day of treatment. The formation of NASH with HCh lasted 90 days. On the forty-fifth day of monotherapy with rosuvastatin in animals of group I, the level of atherogenic lipoproteins decreased, but the activity of liver enzymes and the histological picture did not change significantly. In the second group, a more expressive hypolipidemic effect was found, the concentration of TG was significantly lower compared to group I and the control group, the expressiveness of steatosis was lower. In group III, significant decrease in the levels of TCh, LDL, an increase in HDL, a decrease in the activity of hepatic transaminases, reproduction of the liver structure, and a decrease in steatosis were revealed. The use of rosuvastatin and complex hepatoprotectors led to an expressive lipid-lowering effect and reproduction of the morphological and functional status of the liver in animals with simulated NASH and HCh.